A new flow cytometry assay identifies recipient IgG subtype antibodies binding donor cells: increasing donor availability for highly sensitised patients. Issue 9 (6th September 2022) - Rao, Prakash N; Deo, Dayanand D; Gaur, Amitabh; Baran, David A; Zucker, Mark J; Kapoor, Saurabh; Marchioni, Misty A; Almendral, Jesus; Kandula, Praveen; Patel, Anup
Abstract: Objectives: There are four immunoglobulin (IgG) subtypes that have varying complement‐activating ability: strong (IgG3 and IgG1) and weak (IgG2 and IgG4). The standard flow cytometric crossmatch (FCM) assay does not distinguish between the various subtypes of the IgG molecule. This study outlines the development and use of a novel cell‐based IgG subtype‐specific FCM assay that is able to detect the presence of and quantitate the IgG subtypes bound to donor cells. Methods: A six‐colour lyophilised reagent was designed that specifically detects the four IgG subtypes, as well as distinguishes between T cells and B cells in the lymphocyte population. To test the efficacy of this reagent, a retrospective evaluation of a group of highly sensitised patients awaiting heart and kidney transplant was carried out, who, because of positive standard FCM results, had been deemed incompatible with numerous prior potential donors. Results: Observations in this study demonstrate that the positive standard FCM results were mainly because of the presence of noncomplement‐activating IgG2 or IgG4 antibodies. The results were supported by the absence of C3d‐binding donor‐specific antibodies (DSA) and a negative complement‐dependent cytotoxicity crossmatch (CDC). Conclusion: Preliminary data presented in this study demonstrate the reliability of the novel IgG subtype assay to detect the presence of pretransplant, complement‐activating antibodies bound to donor cells. The knowledge gained from the IgG subtype assay and the C3d‐binding specificities of DSAs provides improved identification of donor suitability in pretransplant patients, potentially increasing the number of transplants. Abstract : In this study, we demonstrate that our novel IgG subtype‐specific FCM assay is able to distinguish between complement‐activating and noncomplement‐activating antibodies bound to donor cells. We observed that in highly sensitised heart and kidney transplant patients, the positive standard FCM results were mainly because of the presence of noncomplement‐binding IgG2 and/or IgG4 antibodies, which was supported by negative CDC assay results and the absence of C3d binding DSAs. Thus, incorporating the IgG subtype assay in the transplant testing regimen for patients awaiting solid organ transplant may aid in increasing donor availability for highly sensitised pretransplant patients.